The Influence of Prabowo's Leadership Communication on Red and White Cabinet - Riyadi, Ilham (Journal of Public Representative and Society Provision, 2024)
This article seeks to examine Prabowo's leadership communication and its effect on the performance of the Red and White cabinet during the initial phase of his presidency, as well as the underlying factors that shaped his communication approach. The analysis employs theories of organizational and leadership communication to provide a comprehensive understanding. Utilizing a qualitative methodology, this research adopts an explanatory case study framework, gathering secondary data from various media sources, academic journals, and relevant documents. The findings indicate that Prabowo's leadership communication style embodies not just a singular model, but rather integrates three distinct models: transformative, transactional, and charismatic all at once. These models are employed by Prabowo within the context of superior-subordinate dynamics with his ministers and staffs. His communication strategies are significantly influenced by his military background and extensive political experience over the past decades. While Prabowo's communication model positively impacts cabinet performance by motivating ministers to pursue government objectives, it also reflects the often-controversial communication styles of his ministers, as evidenced during the early stages of his administration. This underscores the necessity for leaders, including the president, to recognize the critical role of effective leadership communication. Therefore, it is essential for Prabowo to meticulously develop his leadership communication style to facilitate the effective functioning of his cabinet.